Synthesis of CT images from digital body phantoms using CycleGAN [dataset] - Zöllner, Frank G. (Universität, 2022)
The potential of medical image analysis with neural networks is limited by the restricted availability of extensive data sets. The incorporation of...
Gesehen am 18.07.2022
Keywords: Forschungsdaten; Datenbank